Partners in conflict : the United States and Latin America - Lowenthal, Abraham F. (Johns Hopkins University P. BaltimoreUS, 1987)
Argues that present U.S. policy toward Latin America is outdated and out of focus because of the failure of the U.S. to appreciate L.A.'s economic, social and political transformation over the past 25 years. Shows that the primary importance of Latin America to the U.S. lies not in national security but in the region's impact on the U.S. economy. Within this framework demonstrates that U.S. interests are most significant in Mexico, Brazil and the Caribbean. Proposes a new approach towards Latin America and the Caribbean based on policies directed to build cooperative relations.